Relaksasi Fisik dan Psikis: Kombinasi Senam Hamil dan Hypnoterapi dalam Mengurangi Kecemasan Ibu Hamil - Erni Juniartati; Marsia Marsia; Lily Yuniar; Zainab Zainab (Universitas Pahlawan Tuanku Tambusai, 2025)
Anxiety in pregnant women is a common psychological problem caused by physical and emotional changes during pregnancy, especially in the third trimester before delivery. This study aimed to analyze the effectiveness of prenatal exercise and hypnotherapy in reducing anxiety levels among pregnant women. The research used a pre-experimental one-group pretest-posttest design involving 34 third-trimester pregnant women who attended pregnancy classes at Singkawang Utara 1 Public Health Center, West Kalimantan, and Martapura Public Health Center, South Kalimantan. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The results showed that the mean anxiety score decreased from 17.97±5.424 before intervention to 11.24±5.046 after intervention. Statistical analysis indicated a significant difference (p=0.000) with a 37.4% reduction in anxiety scores. This study concludes that the combination of prenatal exercise and hypnotherapy is effective in reducing anxiety levels in third-trimester pregnant women. The intervention can be applied as a non-pharmacological therapy to improve psychological well-being during pregnancy and childbirth preparation.